Using markerless motion analysis to quantify sex and discipline differences in external mechanical work during badminton match play - Santiano, F.; Ison, S.; Emmerson, J.; Colyer, S. (Journal of Sports Sciences, 2025)
The high prevalence of overuse injuries in badminton poses a major threat to player development and success, with current training `load` metrics insufficient for capturing the physical demands. This study quantified the external mechanical work performed during badminton match play across different sexes and disciplines. An eight-camera system captured fourteen male and fourteen female competitive (University to national level) badminton players competing across a total of nine singles and six doubles matches. Markerless pose estimation (HRNet) was used to drive a kinematic model (OpenSim) of each player and compute mass-normalised external mechanical work and power for 30 points per match. A linear mixed effects model found normalised work and power to be greater in men`s vs. women`s matches (effect size [ES] ± 90% CI = 0.60 ± 0.29 and 1.10 ± 0.48, respectively). Normalised work and power were also greater in singles vs. doubles matches (ES = 0.44 ± 0.29 and 0.47 ± 0.44, respectively). Interestingly, discipline differences were greatest among the most skilled players (e.g. ES = 0.88 ± 0.49 for first-team males). These findings highlight the importance of additional strength training and adequate recovery for elite male players to manage the high physical demands of singles match play.